In Situ Green Synthesis of Graphene Oxide-Silver Nanoparticles Composite with Using Gallic Acid - Bao, Yunhui; Tian, Chunlian; Yu, Huazhong; He, Jian; Song, Ke; Guo, Jie; Zhou, Xianwu; Zhuo, Ou; Liu, Shima (Frontiers in Chemistry, 2022)
The adoption of plant-derived natural products to synthesize metal nanoparticles and their complexes has the advantages of mild reaction conditions, environmental protection, sustainability and simple operation compared with traditional physical or chemical synthesis methods. Herein, silver nanoparticles (AgNPs) were in situ synthesized on the surface of graphene oxide (GO) by a “one-pot reaction” to prepare graphene oxide-silver nanoparticles composite (GO-AgNPs) based on using AgNO3 as the precursor of AgNPs and gallic acid (GA) as the reducing agent and stabilizer. The size and morphology of GO-AgNPs were characterized by ultraviolet-visible spectrophotometer (Uv-vis), Fourier transform infrared spectroscopy (FT-IR), transmission electron microscope (TEM), X-ray diffractometer (XRD) and dynamic light scattering (DLS). The effects of pH, temperature, time and material ratio on the synthesis of GO-AgNPs were investigated experimentally. The results showed that ideal GO-AgNPs could be prepared under the conditions of pH=9, 45°C, 2 h and the 2:1 of molar ratio of AgNO3 to GA. The AgNPs within GO-AgNPs are highly crystalline spherical particles with moderate density on the surface of GO, and the size of AgNPs is relatively uniform and determined to be about 8.19±4.21 nm. The research results will provide new ideas and references for the green synthesis of metal nanoparticles and their complexes using plant-derived natural products as the reducing agent and stabilizer.